Combination Of Coagulation-Ultraviolet Photocatalytic Treatment By Using Zinc Oxide With Polyarcylamide And Tannin For Removal Of Colour - Jumahat, Wan Nur Azlin Hanis (Universiti Sains Malaysia, 2019)
Water is an important component in our daily lives. The presence of toxic chemicals and harmful bacteria may expose living things to waterborne diseases and has led a major health risk due to the consumption of contaminated water. Wastewater from the textile industry is one of the many environmental obstructions besides other minor issues like solid waste and resource waste management. There are many types of synthetic dyes that textile industry use and the discharge have massive amounts of highly coloured wastewater. Wastewater with excessive coloured textile sorely effects the photosynthetic function in plant and also impact aquatic lives due to low light penetration and consumption of oxygen. Hence, textile wastewater must be treated properly before being discharged to the environment. In this study, the different treatment methods to treat the textile wastewater is presented. The treatment methods discussed in this study are the coagulation and UV-photocatalytic treatment processes, where both of these methods have been investigated with a combined method. This study involves the modification of zinc oxide with polyacrylamide and tannin as a composite polymer to remove the colour. The objective of this study has been successfully achieved. The modification of composite polymer is prepared as coagulant and catalyst for both treatment methods and it is characterized using the Fourier Transform Infrared Spectroscopy (FTIR) method. The coagulation and photocatalytic activity of ZnO/Tannin/PAM (ZOPAT) using raw textile wastewater is investigated by optimizing parameters such as the effect of pH value, dosage and contact time. The optimum percentage of colour removals obtained for UV-photocatalytic method (93.67%) at 24 hours of treatment period and for combined method (93.92%) at 4 hours of treatment period were achieved at condition of pH 10 and 800 mg/L of the composite polymer dosage. The decolourization of textile wastewater is dependable on the composite polymer used for both treatment methods.